Distinguishing ten sympatric species of fiddler crab (Decapoda: Ocypodidae) using a suite of phenotypic characteristics - Michie, Laura A.; Barnes, R. S. K.; Clark, Paul F.; Bennett, Wayne A.; Cragg, Simon M. (Zootaxa, 2021)
Ten species of fiddler crab are reported inhabiting the intertidal zone of a shore on Kaledupa Island, Indonesia. This is one of the highest recorded numbers of fiddler crab species living in sympatry, equating to over two-thirds of those known from the Wallacea biogeographic region and more than half of all those recorded from Indonesia. The descriptions to identify and distinguish these ten species are provided using a suite of characters e.g., carapace, major cheliped, male gonopods, gastric mills, life colouration in males and females, and notes on their ecology and distribution. Specimens were observed and collected in the Wakatobi National Park, near the village of Ambeua on Kaledupa island, Sulawesi Tenggara, Indonesia. Gastric mills are described for the first time for Gelasimus jocelynae, Paraleptuca crassipes, Tubuca coarctata, T. demani and T. dussumieri. A tabulation of anatomical features and colouration for all species in this study is provided as a support for field studies. It identifies features that support the recently proposed taxonomic revision of fiddler crabs by Shih et al. (2016).